Sistem Pakar Pendeteksi Penyakit Gigi Dan Mulut Dengan Menggunakan Metode Forward Chaining - Wahyuni Fithratul Zalmi (Jurnal Informatika, 2023)
Diseases of the teeth and mouth are one of the many health problems that often interfere with the activities of sufferers. Diseases attack indiscriminately Reed both children and adults. Dental and oral health is an important thing that needs to be considered. Problems that occur in the teeth and mouth must be handled properly so as not to cause other problems that occur due to improper handling. Doctors are required to provide decisions quickly, and accurately in diagnosing diseases suffered by their patients. But to make such a diagnosis is not easy, considering that each disease has more than one symptom, and several different diseases have almost the same symptoms. Decision - making in diagnosing the disease carefully and appropriately must be done quickly for the treatment process of the disease. Especially for young doctors and all doctors if they find cases that are difficult to diagnose, they will generally be guided by books. This will certainly take time and effort. Treatment for this problem is to build an expert system application that functions to diagnose diseases of the teeth and mouth. This expert system application is expected to help doctors in deciding to diagnose diseases quickly or become a matter of consideration or reference.